Literasi gizi seimbang untuk wanita usia subur pada masa pandemic COVID-19 - Tri Siswati; Khoirunnisa Rahmawati (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
In pandemic Covid-19, implementing balanced nutrition is fundamental, it support people health and improve endurance. Education, information and communication is method to change human behavior.  This was a community engagement to facilitate participant increase knowledge and awareness of balanced diet especially during pandemic covid-19. The event was held on the January 23th-25th 2021 in Wirokerten village, Bantul district, DI Yogyakarta. Education carried out  online with a link goegle-meet. The participants were women reproductive age as many as 20 people. Material education were balanced nutrition, food against covid-19 and increase food security using planting of vegetable and local fruit. Pre and post test were implemented to identified the program evaluation. Result show that education, information and communication increase knowledge by 40%. Virtual Education, information and communication is an effective method to increase participant’s knowledge during Covid-19 pandemic.